2015
DOI: 10.1016/j.neuroscience.2015.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and morphological changes in the dorsal hippocampus of very old female rats

Abstract: The hippocampus, a medial temporal lobe structure necessary for the formation of spatial memory, is particularly affected by both normal and pathologic aging. In previous studies, we observed a significant age-related increase in dopaminergic neuron loss in the hypothalamus and the substantia nigra of female rats, which becomes more conspicuous at extreme ages. Here, we extend our studies by assessing spatial memory 4–6 months old (young), 26 months old (old) and 29–32 months old (senile) Sprague–Dawley female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 41 publications
4
64
0
12
Order By: Relevance
“…39,41 Moreover, episodic-like memory was assessed by the novel object recognition test, which deals with the natural ability of animals to explore novelties. 32 Consistent with previous observations, 6,7,29,42 aged control rats showed an impairment of cognitive abilities, including working memory in the radial maze, episodic-like memory on the novel object recognition test and spatial learning on the Barnes maze test. Nevertheless, a significant improvement of these memory tasks was observed after treatment with the higher dose of α-tocopherol analyzed.…”
Section: Discussionsupporting
confidence: 87%
“…39,41 Moreover, episodic-like memory was assessed by the novel object recognition test, which deals with the natural ability of animals to explore novelties. 32 Consistent with previous observations, 6,7,29,42 aged control rats showed an impairment of cognitive abilities, including working memory in the radial maze, episodic-like memory on the novel object recognition test and spatial learning on the Barnes maze test. Nevertheless, a significant improvement of these memory tasks was observed after treatment with the higher dose of α-tocopherol analyzed.…”
Section: Discussionsupporting
confidence: 87%
“…They are one of the most common rodent strains in toxicological research, and the studies described herein are part of the larger CLARITY-BPA studies where all investigators are using this animal model (Birnbaum et al, 2012; Heindel et al, 2015; Schug et al, 2013). Additionally, SD rats are widely used in various Barnes maze experiments (Barrett et al, 2009b; Locklear and Kritzer, 2014; Morel et al, 2015), including those performed at the NCTR (Ferguson et al, 2012), and we sought to compare the current findings to those prior studies.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it has been reported that the accuracy to remember the escape hole in the Barnes maze declines with age in female rats, a change that is paralleled by an age-related reduction in the numbers of doblecortin (DCX) neurons in the DG. 28 In 28 months old male Brown Norway X Fischer 344 rats, a significant reduction in the number of newly generated cells was reported in the DG as well as a 60% reduction in diferentiation of newborn cells into neurons. 29 In the same study it was demonstrated that ICV administration of IGF-I peptide to old animals, signifcantly restored neurogenesis in the DG through an approximately 3-fold increase in neuronal production, without having any effect on progenitor differentiation to neurons or on survival of newborn cells.…”
Section: Igf-i Gene Therapy and Neurogenesis In The Dentate Gyrus (Dgmentioning
confidence: 99%
“…31 In an earlier study, an age-related reduction in length and complexity of hippocampal astrocyte processes in female rats was reported. 28 Reduced branching in aged astrocytes may impair the ability of these cells to provide trophic support to neurons. Therefore, the finding that IGF-I gene delivery to the brain of old rats restores complexity (but not length) of glial processes in the hippocampus, suggests that this effect may contribute to improving neuronal function in the region.…”
Section: Igf-i Gene Therapy and Neurogenesis In The Dentate Gyrus (Dgmentioning
confidence: 99%